Economia do crime: uma revisão teórica e análise das despesas públicas em segurança no Ceará (2006-2010) - Maria, Jônatas Garcia de (2012)
This paper seeks to review the theoretical assumptions of the Economics of Crime and it´s based on these models and analyze the data for the State of Ceará between 2006 and 2010. The main findings and conclusions point to the fact that the State of Ceará, despite high investments in public safety between the years 2006 to 2010, hasn´t achieved a satisfactory level, pursued through the implementation of the latest public spending policies. In the short term these policies are effective, however, alone, can´t be sustained over longer periods, ie, other strategies are needed to decrease crime rates.